The 100 : a ranking of the most influential persons in history the 100 - Hart, Michael H. (London Simon & Scuster, 1992)
A list of the one hundred most influential people in history features descriptions of the careers, contributions, and accomplishments of the political and religious leaders, inventors, writers, artists, and others who changed the course of history. Simult Title: The 100 Author: Hart, Michael H. Publisher: Kensington Pub Corp Publication Date: 1992/10/01 Number of Pages: Binding Type: PAPERBACK Library of Congress: 92035426.